Electroplated Ni coated carbonyl iron powder corrosion-resistant absorbent and preparation method thereof
By electroplating Ni coated carbonyl iron powder, the problem of radar wave absorbers being easily corroded in marine environments is solved, the corrosion resistance and wave absorption properties of the material are significantly improved, and the high standard requirements under extreme marine conditions are met.
Patent Information
- Application Number
- CN202411829862.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-01
AI Technical Summary
Existing radar wave absorbers are prone to corrosion in marine environments, resulting in a degradation of wave absorption performance and cannot meet the high standards requirements under extreme marine conditions.
By electroplating Ni coated carbonyl iron powder, the corrosion resistance of the material is improved while maintaining excellent wave absorption characteristics. The method includes pretreatment of the carbonyl iron powder, electroplating of nickel layer, heat treatment and passivation treatment.
In harsh marine environments with high temperature, high humidity and high salt spray content, electroplating Ni coated carbonyl iron powder significantly improves the corrosion resistance of the material, extends the service life, and maintains good radar wave absorption performance.
Smart Images

Figure CN119736683A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, and particularly relates to a Ni-plated carbonyl iron powder corrosion-resistant absorbent and a preparation method thereof. Background Art
[0002] With the continuous advancement of science and technology, modern sensor technology is rapidly developing towards higher accuracy, finer precision and more advanced directions. Radar detection technology, as a key component, accurately determines the position of a target by analyzing the electromagnetic waves reflected back by the target. In order to counter this efficient detection method, radar wave absorbing materials have emerged. Such materials can convert the incident electromagnetic energy into heat energy for dissipation or reduce the reflection intensity of electromagnetic waves through the interference destructive mechanism, thereby achieving effective stealth against radar.
[0003] The core of the absorbing material is the absorber, which is usually composed of metal micropowder (such as carbonyl iron), ferrite materials, silicon carbide ceramic materials, conductive polymer materials and nanomaterials. Carbonyl iron has been widely used in radar wave absorbing materials because of its high microwave magnetic permeability, thin matching thickness, good thermal stability and high saturation magnetization. However, in the actual application of military equipment such as carrier-based aircraft, these materials need to face the harsh marine environment of high temperature, high humidity and high salt spray content, which will cause the absorbing performance of carbonyl iron powder to decrease, thereby affecting the performance of the overall material. Therefore, improving the corrosion resistance of carbonyl iron powder has become one of the key issues.
[0004] The existing anti-corrosion methods may have an adverse effect on the electromagnetic absorbing performance of carbonyl iron powder. In view of this, it is particularly important to develop a technology that can effectively enhance the ability of carbonyl iron powder to resist seawater corrosion without significantly reducing the electromagnetic absorbing performance. Although the existing patent "A rust-resistant carbonyl iron powder absorbing material and its preparation method" CN113388231A proposes a solution to the problem of rust in absorbing materials prepared from carbonyl iron powder under complex working conditions such as military and civilian fields, it is not specifically optimized for the problem of marine environment, especially seawater corrosion; similarly, the patent "A carbonyl iron powder composite absorbing material and its preparation method" CN112374547A introduces a method of using silicon dioxide to coat carbonyl iron powder to improve its magnetic and mechanical properties, but it also does not fully consider how to deal with the challenges brought by seawater corrosion.
[0005] In summary, there is an urgent need to develop a new generation of radar wave absorbers that have good corrosion resistance, excellent wave absorbing effect and low cost, so as to meet the high standards required for use under extreme marine conditions. Summary of the invention
[0006] The purpose of the embodiment of the present invention is to provide a Ni-plated carbonyl iron powder corrosion-resistant absorber and a preparation method thereof, so as to solve the problem of decreased wave absorbing performance of carbonyl iron powder due to corrosion in harsh marine environments such as high-salinity seawater, thereby improving the overall performance of the radar wave absorber.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is a method for preparing a corrosion-resistant absorbent of electroplated Ni-coated carbonyl iron powder, which is specifically carried out in the following steps:
[0008] S1. Pre-treating the carbonyl iron powder to remove surface oxides and impurities;
[0009] S2, preparing an electroplating solution containing nickel ions, and depositing a nickel layer on the surface of the carbonyl iron powder by electroplating;
[0010] S3, performing heat treatment and passivation treatment on the nickel-plated carbonyl iron powder to obtain nickel-coated carbonyl iron powder.
[0011] Furthermore, the specific steps of S1 are as follows:
[0012] S101, soak the carbonyl iron powder in a pickling solution at 25-35°C for 5-10 minutes;
[0013] S102, washing the pickled carbonyl iron powder with deionized water to remove the acid solution and surface impurities;
[0014] S103, placing the cleaned carbonyl iron powder in a vacuum drying device, and drying at 80-100° C. for 30-60 minutes, wherein the vacuum pressure during vacuum drying is ≤0.01 MPa.
[0015] Furthermore, the pickling solution is composed of hydrochloric acid or sulfuric acid solution with a mass concentration of 10% to 20%.
[0016] Furthermore, the specific steps of S2 are as follows:
[0017] S201, adding nickel salt, buffer and deionized water into a magnetic stirrer for stirring, wherein the stirring rate of the magnetic stirrer is 750-850 rpm and the duration is 30-40 min;
[0018] Then add complexing agent, brightener and wetting agent in sequence, and finally add pH adjuster to adjust the acid-base environment to between 3-5, and transfer to the electroplating tank after adjustment;
[0019] S202, placing the carbonyl iron powder pretreated in S1 in an electroplating tank, using a DC power supply for electroplating; and using a filter to circulate the electroplating solution to evenly disperse the electroplating solution;
[0020] S203, after the nickel plating is completed, the carbonyl iron powder is taken out from the electroplating tank, and is cleaned with deionized water, and then dried after cleaning; the drying temperature is 80-100° C., and the drying time is 20-40 minutes.
[0021] Further, in S201, the nickel salt is a combination of nickel chloride and nickel sulfate; wherein the concentration of nickel sulfate is 200-300 g / L; and the concentration of nickel chloride is 20-60 g / L;
[0022] The buffer is boric acid with a concentration of 30-40 g / L.
[0023] Further, in S201, the complexing agent is one of sodium citrate and ethylenediaminetetraacetic acid, and the concentration range of the complexing agent addition is 10 to 15 g / L;
[0024] The brightener is one of nickel sulfate and naphthol, and the concentration range of the brightener addition is 0.3-0.6 g / L;
[0025] The wetting agent is any one of isooctyl alcohol sulfonate, sodium dodecyl sulfonate, and polyvinyl alcohol, and the addition amount of the wetting agent is 0.3 g / L to 0.8 g / L;
[0026] The isooctyl alcohol sulfonation product includes one of sodium isooctyl alcohol sulfonate, potassium isooctyl alcohol sulfonate and isooctyl alcohol sulfonate ester.
[0027] Furthermore, during the S202 electroplating process, the current density is controlled at 2-10A / dm 2 The electroplating time is 30 to 60 minutes; the filter cartridge of the filter is made of PP, and the temperature of the electrolytic cell is 50 to 60°C.
[0028] Furthermore, the specific steps of S3 are as follows:
[0029] S301, placing the nickel-plated carbonyl iron powder in a vacuum drying oven for heat treatment, and cooling the carbonyl iron powder to room temperature after the heat treatment; the heat treatment temperature is 350-450° C., and the heat treatment temperature is 10-12 hours;
[0030] S302, soaking the heat-treated nickel-plated carbonyl iron powder in a passivation solution containing chromate or molybdate for passivation, and then cleaning and drying.
[0031] Further, the concentration of chromate or molybdate in the passivation solution in S302 is 50-150 g / L;
[0032] The chromate is one of potassium dichromate and sodium dichromate;
[0033] The molybdate is one of sodium molybdate, potassium molybdate and ammonium molybdate.
[0034] A corrosion-resistant absorbent of electroplated Ni-coated carbonyl iron powder prepared by the above method.
[0035] Compared with the prior art, the present invention provides a technology for preparing electroplated nickel (Ni) coated carbonyl iron powder by an electroplating method. The present invention improves the corrosion resistance of the radar wave absorbing material while maintaining its excellent wave absorbing properties.
[0036] Specifically, the present invention includes the following beneficial effects:
[0037] 1. The present invention coats the carbonyl iron powder with an electroplated nickel layer, which effectively improves the corrosion resistance of the material in harsh marine environments such as high temperature, high humidity and high salt spray content. This not only extends the service life of the material, but also ensures the stability and reliability of the radar wave absorber under extreme conditions.
[0038] 2. The design of the electroplated nickel coating layer of the present invention takes into account the influence on the electromagnetic wave absorption performance. By optimizing the thickness and uniformity of the nickel layer, it is ensured that the material will not significantly reduce its microwave magnetic permeability and wave absorption efficiency while improving the corrosion resistance. Therefore, the present invention can further improve the overall performance of the material while maintaining the original wave absorption performance.
[0039] 3. Compared with the prior art, the electroplating process used in the present invention is relatively simple and easy to control, which reduces production costs. In addition, the introduction of the electroplated nickel coating reduces the maintenance requirements of the material during use, thereby reducing long-term operating costs.
[0040] 4. The electroplating process adopted by the present invention meets environmental protection requirements, and the chemical reagents and process conditions used are strictly screened to reduce the emission of harmful substances. At the same time, the waste liquid generated during the electroplating process can be effectively treated by existing wastewater treatment technology, reducing the impact on the environment.
[0041] 5. Since the electroplated nickel-coated carbonyl iron powder has good corrosion resistance and wave absorbing properties, the radar wave absorbent coating of the present invention can be widely used in multiple high-tech fields such as communications, aerospace, etc. In particular, it can significantly improve the stealth capability and survivability of these platforms in military equipment such as carrier-based aircraft and ships.
[0042] 6. The electroplating process parameters (such as current density, temperature, time, etc.) of the present invention can be precisely controlled to ensure the consistency and uniformity of the coating layer. This high degree of process controllability makes large-scale production and quality control possible, ensuring the stability and consistency of the product.
[0043] In summary, the present invention not only solves the problem of the existing radar wave absorbers being easily corroded in marine environments, but also provides a low-cost, environmentally friendly and high-performance solution while maintaining excellent wave absorbing performance. This opens up a new path for the application of radar wave absorbing materials in extreme environments and is expected to play an important role in many fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 is the element distribution diagram of the Ni-coated carbonyl iron powder obtained in Example 1;
[0046] Figure 2 is a backscattered electron photograph of the Ni-coated carbonyl iron powder obtained in Example 1;
[0047] Figure 3 1 is a comparison diagram of electromagnetic parameters of the Ni-coated carbonyl iron powder obtained in Example 2 before and after corrosion, (a) is the change of the real part of the dielectric constant with frequency (GHz), (b) is the change of the imaginary part of the dielectric constant with frequency (GHz), (c) is the change of the real part of the magnetic permeability with frequency (GHz), (d) is the change of the imaginary part of the magnetic permeability with frequency (GHz);
[0048] Figure 4 This is a comparison diagram of the electromagnetic parameters of the non-Ni-coated carbonyl iron powder obtained in Example 1 before and after corrosion, (a) is the change of the real part of the dielectric constant with frequency (GHz), (b) is the change of the imaginary part of the dielectric constant with frequency (GHz), (c) is the change of the real part of the magnetic permeability with frequency (GHz), and (d) is the change of the imaginary part of the magnetic permeability with frequency (GHz). DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Since the existing carbonyl iron powder is easily corroded in the marine environment, especially the high-salinity seawater corrosion can cause the carbonyl iron powder to have a reduced wave absorbing performance, thereby causing the overall performance of the absorber to be damaged, this embodiment provides a carbonyl iron powder nickel plating process for radar wave absorbers, comprising the following steps:
[0051] S1. Pre-treating the carbonyl iron powder, including removing surface oxides and impurities;
[0052] S101, soaking the carbonyl iron powder in a pickling solution; the pickling solution is a dilute solution of hydrochloric acid or sulfuric acid (mass concentration is 10% to 20%), the soaking time is 5 to 10 minutes, and the pickling temperature is controlled at 25 to 35°C. The purpose of this treatment step is to remove the oxide layer and other impurities on the surface of the carbonyl iron powder to ensure that its surface is highly clean, thereby optimizing the performance in subsequent processing or application.
[0053] In some specific embodiments, the concentration and reaction temperature of hydrochloric acid or sulfuric acid solution must be strictly controlled. Both acids are strongly acidic substances, can react chemically with the oxide on the metal surface, generate soluble salts, thereby effectively removing rust. In addition, hydrochloric acid or sulfuric acid also have the ability to dissolve some water-insoluble metal oxides and hydroxides, further enhancing the rust removal effect. However, since hydrochloric acid or sulfuric acid has strong corrosivity to metal matrix, its concentration and processing time need to be strictly controlled in the rust removal process to avoid excessive corrosion of the metal matrix.
[0054] S102, washing the carbonyl iron powder after pickling with deionized water to remove residual acid and impurities;
[0055] S103, placing the cleaned carbonyl iron powder in a vacuum drying device, and drying it at 80-100° C. for 30-60 minutes. The vacuum pressure during vacuum drying is ≤0.01 MPa. This is to prevent the carbonyl iron powder from being oxidized or corroded.
[0056] In order to maintain the microwave absorption properties of carbonyl iron powder, the drying process must be carried out in an oxygen-free environment and the temperature must be strictly controlled between 80 and 100°C. This is because the oxidative environment at high temperature will damage the performance of carbonyl iron powder, and too high a temperature may also reduce its magnetic permeability, thus affecting the effect in practical applications. In addition, it is crucial to ensure that the carbonyl iron powder is completely dried, because residual moisture will weaken its antioxidant and acid and alkali resistance. At the same time, thorough drying also helps to avoid agglomeration caused by interactions between particles and ensure uniform dispersion of the powder.
[0057] S2, using an electroplating solution containing nickel ions to deposit a nickel layer on the surface of the carbonyl iron powder by electroplating;
[0058] S201. Add nickel sulfate (NiSO4·6H2O), nickel chloride (NiCl2·6H2O), and boric acid (H3BO3) to a magnetic stirrer, add deionized water, and stir for a certain period of time to dissolve evenly. Then add a complexing agent solution to help nickel ions deposit evenly. Add a brightener to make the surface of the electroplated layer brighter and more uniform. Then add a wetting agent and pH regulator ammonia water to improve the quality of the coating and process stability, and control the acid-base environment. After the adjustment is completed, add it to the electroplating tank.
[0059] In some possible embodiments, the nickel salt is a combination of nickel chloride and nickel sulfate; as a source of nickel element, it provides nickel ions for the entire reaction. In this embodiment, the type of nickel salt is selected mainly based on cost considerations, but its content must be precisely controlled: too high a nickel salt concentration may cause the coating structure to collapse or form an overly thick coating, thereby significantly reducing the saturation magnetization of the material; and insufficient content cannot achieve an effective coating effect. Therefore, in order to ensure the stability and uniformity of the coating layer, this embodiment introduces another nickel salt as a stabilizer to optimize the entire coating process.
[0060] In some specific embodiments, the concentration of nickel sulfate (NiSO4·6H2O) in step S201 needs to be controlled at 200-300 g / L, nickel chloride (NiCl2·6H2O) needs to be controlled at 20-60 g / L, and the buffer boric acid (H3BO3) needs to be controlled at 30-40 g / L. The magnetic stirring rate is 750-850 rpm and lasts for 30-40 minutes.
[0061] The buffer is boric acid. In this embodiment, the use of boric acid can effectively control the pH value within a certain range, prevent the local pH value from increasing due to hydrogen precipitation, thereby avoiding the formation of nickel hydroxide precipitation and improving the quality of the coating. Boric acid not only has a buffering effect, but also can improve the mechanical properties and cathode polarization of the coating. If the buffer is selected from citrate, acetic acid and its salts, potassium, calcium or zinc impurities will be introduced into the coating. In this embodiment, the amount of buffer introduced is strictly controlled. Too high a buffer content will cause defects in the Ni coating, such as roughness and increased brittleness. This is because an excessive amount of buffer forms a precipitate near the cathode region, which not only hinders the further reduction of nickel ions, but also may cause impurities to be included in the coating, thereby affecting the mechanical properties of the coating. When the buffer content is too low, its buffering effect will be significantly weakened, causing the pH value of the plating solution to become unstable. This instability of the pH value will cause the pH value of the cathode solution to rise, thereby affecting the quality of the electroplating layer.
[0062] In some possible implementations, the complexing agent is one of sodium citrate and ethylenediaminetetraacetic acid (EDTA); its function is to prevent precipitation, provide good dispersibility and brightening effect, and improve the stability of the plating solution.
[0063] In some specific embodiments, the concentration of the complexing agent is in the range of 10-15 g / L. If the complexing agent is added in excess, the complexing agent will form an overly stable complex with nickel ions, thereby significantly reducing Ni 2 +, slowing down the Ni 2 +The speed at which nickel migrates to the cathode and deposits as metallic nickel will not only reduce the electroplating efficiency, but also lead to a low actual concentration of nickel salt in the plating solution, further affecting the uniformity and density of the coating, and ultimately damaging the physical and chemical properties of the coating. On the contrary, if the complexing agent is not added enough, the activity of nickel ions cannot be effectively controlled, resulting in uneven distribution of nickel ions in the solution, inconsistent deposition of the coating, and defects such as spots or stripes. This unevenness will affect the appearance quality of the coating, and due to the uneven thickness of the coating, its corrosion resistance and other protective properties will also be affected, which is not conducive to the long-term stability and reliability of the product. Therefore, in the electroplating process, the amount of complexing agent must be precisely controlled to ensure that nickel ions can be evenly deposited at an appropriate rate, so as to obtain a high-quality, high-performance nickel coating.
[0064] In some possible embodiments, the brightener is one of nickel sulfate and naphthol; its function is to increase the surface activity of the cathode, promote the deposition of nickel ions, form a complex and improve the conductivity. This embodiment introduces a brightener into the electroplating solution to promote the formation of a high-brightness and corrosion-resistant oxide film, so that the surface brightness of the electroplated layer is higher and more uniform; the electroplated layer with higher brightness has better surface uniformity and fewer surface defects (such as pinholes, depressions or rough surfaces). The uniform coating can provide better adhesion, thereby improving the corrosion resistance of the Ni coating.
[0065] In some specific embodiments, the addition amount (concentration) of the brightener is in the range of 0.3-0.6g / L, and the concentration of the brightener has a direct impact on the mechanical properties, corrosion resistance and appearance quality of the coating. If the concentration of the brightener is too high, it may cause the internal stress of the coating to increase, thereby weakening the robustness of the coating and possibly reducing its corrosion resistance. In addition, too high a brightener concentration may also cause the bonding force between the coating and the substrate to weaken, causing the coating to bubble, peel off or unevenly deposited. On the contrary, if the concentration of the brightener is too low, it is not possible to effectively refine the grains and improve the microstructure of the coating surface, resulting in an increase in the surface roughness of the coating, affecting the smoothness and glossiness of the coating, and also causing uneven distribution of the coating thickness, further affecting the quality and functionality of the coating. Therefore, the present embodiment accurately adjusts the addition amount of the brightener to optimize the electroplating process parameters, improve product quality, and ensure that a high-quality coating with both excellent appearance and good mechanical properties and corrosion resistance is obtained.
[0066] In some possible embodiments, the wetting agent is any one of sodium alkylbenzene sulfonate, sodium dodecyl sulfonate, and polyvinyl alcohol, which are sulfonated products of isooctyl alcohol; its function is to reduce the surface tension of the plating solution, enhance the contact between the plating solution and the surface of the plated object, and prevent bubble adhesion, thereby improving the coating quality and process stability.
[0067] In some possible implementations, the isooctyl alcohol sulfonation product specifically includes one of sodium isooctyl alcohol sulfonate, potassium isooctyl alcohol sulfonate, and isooctyl alcohol sulfonate ester.
[0068] In some specific embodiments, the amount of wetting agent added is 0.3g / L to 0.8g / L. If the wetting agent concentration is too high, the surface tension of the electroplating solution will be significantly reduced, thereby causing the formation of too many bubbles, which will interfere with the electroplating process, causing uneven deposition of the coating, and introducing tiny defects in the coating. In addition, excessive wetting agent will make the surface of the Ni coating too smooth, thereby weakening the adhesion between the coating and the substrate, reducing its corrosion resistance, and ultimately affecting the long-term stability and functionality of the coating. On the contrary, if the wetting agent concentration is too low, the surface tension of the electroplating solution cannot be effectively reduced, resulting in excessive surface tension, which will affect the migration and deposition behavior of metal ions, causing uneven deposition of the Ni coating, thickness differences or surface defects.
[0069] In some possible implementations, the pH adjuster is ammonia water, which provides hydroxide ions for adjusting hydrogen ions in the buffer and controlling the acid-base environment so that the pH value is between 3-5.
[0070] This embodiment adjusts the pH value to between 3-5, which can significantly reduce defects such as holes and cracks in the coating, thereby greatly improving the density and uniformity of the coating. In the pH range of 3 to 5, the Ni coating can show a lower porosity and defect density. This dense coating structure effectively blocks the erosion path of seawater to the substrate, significantly enhancing the material's resistance to seawater corrosion. In addition, this embodiment finds that a pH value in the range of 3 to 5 helps to optimize the interface bonding between the Ni coating and the carbonyl iron powder, promotes the formation of a stable chemical bond between the two, and thereby improves the adhesion and mechanical bonding strength of the Ni coating. This not only reduces the potential corrosion channels formed by interface peeling or cracking, but also further enhances the overall protective effectiveness of the coating. Therefore, this embodiment accurately controls the pH value within the range of 3-5, which is of key significance for obtaining a high-performance, long-life anti-corrosion coating.
[0071] S202, placing the pretreated carbonyl iron powder in an electroplating tank, using a DC power supply for electroplating, and using a filter to stir the solution in a filtrate circulation manner, thereby improving the mixing uniformity of the solution, promoting the material transfer process, eliminating concentration polarization, and increasing the current density.
[0072] In some specific embodiments, the current density in S202 is controlled at 2 to 10 A / dm 2 , the electroplating time is 30 to 60 minutes, and the specific time needs to be adjusted according to the thickness requirements of the nickel plating layer. During the electroplating process, a filter needs to be used to evenly stir the electroplating solution to ensure the uniformity and density of the nickel plating layer. The filter capacity is 15 liters / minute, and a PP filter cartridge is used. The electrolytic cell temperature is 50 to 60°C.
[0073] In this embodiment, the current density and time in S202 need to be strictly controlled; during the electroplating process, the uneven distribution of current density will cause the thickness of the coating to be inconsistent on the metal substrate. A higher current density can accelerate the deposition process of the coating, but it will also cause defects such as bubbles and cracks on the surface of the coating. In order to obtain a uniform coating with a certain thickness, this embodiment reasonably adjusts the current density so that it remains stable during the entire electroplating process. In addition, the current density also has an important influence on the composition and composition distribution of the coating. Changes in current density can affect the reduction rate and deposition rate of metal ions, and thus affect the composition of the coating. For example, during the electroplating process, a higher current density will cause the impurity ions in the plating solution to be reduced and deposited faster, resulting in an increase in the impurity content in the coating.
[0074] In addition, too high a current density may cause the electroplating layer to be too thick and may cause the metal surface to burn; too low a current density may cause the electroplating layer to be too thin or even not electroplated. The length of the electroplating time directly affects the thickness of the electroplating layer. Too long an electroplating time may make the electroplating layer too thick, while too short an electroplating time may make the electroplating layer too thin. Too low a current density will lead to low nickel deposition rate and efficiency, and the resulting nickel plating layer will have a high porosity, which may not only weaken the mechanical strength and corrosion resistance of the plating layer, but may also reduce the hardness of the plating layer, thereby affecting its wear resistance and impact resistance.
[0075] S203, after the nickel plating is completed, the carbonyl iron powder is taken out from the electroplating tank, and washed with deionized water to remove the electroplating solution remaining on the surface. The washed carbonyl iron powder needs to be dried.
[0076] In some specific embodiments, the drying temperature in S203 needs to be controlled at 80-100°C, and the drying time is 20-40 minutes; if the drying temperature is set too low, it will not only extend the drying time and affect production efficiency, but also may damage product quality due to residual moisture. On the contrary, if the drying temperature is too high, it may cause oxidation reaction of carbonyl iron powder that has not yet been fully combined with the nickel coating. Since the protective effect of the nickel coating on the carbonyl iron powder is not sufficient at this time, the surface of the carbonyl iron powder is easily oxidized under high temperature conditions, which in turn affects the performance and quality of the final product.
[0077] S3. The nickel-plated carbonyl iron powder is subjected to heat treatment and passivation treatment to improve the bonding strength and corrosion resistance of the nickel layer.
[0078] S301, placing the nickel-plated carbonyl iron powder in a vacuum drying oven for heat treatment, and cooling the carbonyl iron powder to room temperature after the heat treatment;
[0079] In some specific embodiments, in S301, the nickel-plated carbonyl iron powder is placed in a vacuum drying oven and heat-treated at a temperature of 350 to 450° C. for 10 to 12 hours. After the heat treatment, the carbonyl iron powder needs to be cooled to room temperature. The purpose of this is to further improve the bonding strength and corrosion resistance of the nickel coating and the carbonyl iron powder matrix.
[0080] In this embodiment, the heat treatment in S301 needs to be allowed to cool naturally in the furnace, otherwise excessive internal stress will be caused due to excessive temperature changes, thereby affecting product quality.
[0081] S302, soaking the heat-treated nickel-plated carbonyl iron powder in a passivation solution containing chromate or molybdate for passivation, and then cleaning and drying.
[0082] In some specific embodiments, the nickel-plated carbonyl iron powder after heat treatment in S32 is immersed in a passivation solution containing 50-150 g / L of chromate or molybdate, and the passivation time should be 10-20 minutes. The purpose of this is to improve the corrosion resistance and stability of the coating. The chromate is one of potassium dichromate and sodium dichromate; the molybdate is one of sodium molybdate, potassium molybdate, and ammonium molybdate.
[0083] In this embodiment, heat treatment is to impart or improve the performance of the material by changing the microstructure of the material or changing the chemical composition of the material surface; in order to make the material have the required mechanical properties, physical properties and chemical properties, if the heat treatment step is abandoned during S301, it will have a certain impact on the final morphology and shrinkage state of the material. At the same time, the mechanical, physical and chemical properties of the material are further changed by heat treatment, and the bonding force and corrosion resistance of the nickel coating and the carbonyl iron powder matrix are improved. In addition, high temperature helps the atomic diffusion between nickel and carbonyl iron powder, thereby enhancing the metallurgical bonding between the two. At the same time, it can promote phase change in the nickel coating to form a more dense and uniform microstructure.
[0084] Example 1
[0085] S1. Pretreatment of carbonyl iron powder
[0086] S101. Select carbonyl iron powder with an average particle size of 20 microns and a purity of 99.5%, which is suitable for the production of radar wave absorbers.
[0087] S102, place 100 grams of carbonyl iron powder in 500 milliliters of hydrochloric acid solution, the concentration of which is 15%. Soak for 7.5 minutes at 30°C. The purpose of pickling is to remove oxides and other impurities on the surface of the carbonyl iron powder. After pickling, remove the carbonyl iron powder from the acid solution and wash it with deionized water for 3 times, each time for 2 minutes, to ensure that the residual acid and impurities on the surface of the carbonyl iron powder are completely removed.
[0088] S103, placing the cleaned carbonyl iron powder in a vacuum drying oven, and drying at 90° C. and a vacuum pressure of 0.01 MPa for 45 minutes until the surface of the carbonyl iron powder is completely dry; preventing the carbonyl iron powder from being oxidized or rusted.
[0089] S2. Nickel plating of carbonyl iron powder
[0090] S201. Place 200g of nickel sulfate (NiSO4·6H2O), 20g of nickel chloride (NiCl2·6H2O), and 30g of boric acid (H3BO3) in a magnetic stirrer, add 1L of deionized water, and stir for a certain period of time to make it evenly dissolved. Then add 12.5g of complexing agent solution sodium citrate to help nickel ions deposit evenly. Add 0.45g of brightener nickel sulfate to make the surface brightness of the electroplated layer higher and more uniform. Then add 0.55g of wetting agent isooctyl sulfonate and pH adjuster ammonia water to improve the quality of the plating layer and process stability, and control the acid-base environment. The pH value of the electroplating solution is adjusted to 3.0 and the temperature is controlled at 55°C.
[0091] S202, put the pretreated carbonyl iron powder into a nickel plating electrolytic cell, and keep the plating solution temperature at 55°C. The electroplating adopts a DC power supply, and the current density is controlled at 6A / dm 2 , the electroplating time is 45 minutes. During the electroplating process, the electroplating solution is evenly stirred using a filter. The filter capacity is 15 liters / minute, and a PP filter cartridge is used. The electrolytic cell temperature is 50°C. The electroplating solution needs to be continuously stirred using a filter to ensure uniform deposition of the nickel coating on the surface of the carbonyl iron powder. After the electroplating is completed, the nickel-plated carbonyl iron powder is removed from the electrolytic cell using a filter.
[0092] S203, washing the nickel-plated carbonyl iron powder with deionized water for 3 times, 2 minutes each time, to remove the plating solution residue. Then, drying the washed carbonyl iron powder at 90° C. for 40 minutes until the carbonyl iron powder is completely dry.
[0093] S3, post-processing
[0094] S301, placing the dried nickel-plated carbonyl iron powder in a vacuum drying oven and heat treating it at 350° C. for 12 hours. After the heat treatment, the carbonyl iron powder is naturally cooled to room temperature.
[0095] S302, the heat-treated carbonyl iron powder is placed in a passivation solution containing sodium molybdate (sodium molybdate concentration is 150 g / L) and soaked at room temperature for 15 minutes. After passivation, the carbonyl iron powder is washed with deionized water and dried again.
[0096] S4. Result detection
[0097] Scanning electron microscope observation showed that a uniform and dense nickel layer was formed on the surface of the nickel-plated carbonyl iron powder. After the nickel-plated carbonyl iron powder was immersed in artificial seawater (3.5% NaCl solution) for 1000 hours, no obvious corrosion was found. Further electromagnetic wave absorption performance tests showed that the nickel-plated carbonyl iron powder had good absorption performance in the radar wave frequency band (2-18GHz), meeting the application requirements of radar wave absorbers.
[0098] Figure 1 This is the element distribution diagram of the nickel-coated carbonyl iron powder according to Example 1. It can be observed that the surface of the carbonyl iron powder is coated with a uniform and dense nickel coating. Figure 2 This is a microscopic morphology picture of the nickel-coated carbonyl iron powder in Example 1. It can be seen from the picture that the outer surface of the carbonyl iron powder is coated with a uniform, dense and continuous nickel coating, and the thickness of the nickel coating is about 3 microns.
[0099] Example 2
[0100] S1. Pretreatment of carbonyl iron powder
[0101] S101. Select carbonyl iron powder with an average particle size of 20 microns and a purity of 99.5%, which is suitable for the production of radar wave absorbers.
[0102] S102, place 200 grams of carbonyl iron powder in 1000 milliliters of hydrochloric acid solution, the concentration of which is 20%. Soak for 10 minutes at 35°C. The purpose of pickling is to remove oxides and other impurities on the surface of the carbonyl iron powder. After pickling, remove the carbonyl iron powder from the acid solution and wash it with deionized water for 3 times, each time for 2 minutes, to ensure that the residual acid and impurities on the surface of the carbonyl iron powder are completely removed.
[0103] S103, placing the cleaned carbonyl iron powder in a drying oven, and drying it at 100° C. and a vacuum pressure of 0.01 MPa for 60 minutes until the surface of the carbonyl iron powder is completely dry, in order to prevent the carbonyl iron powder from being oxidized or corroded.
[0104] S2. Nickel plating of carbonyl iron powder
[0105] S201. Place 250g of nickel sulfate (NiSO4·6H2O), 40g of nickel chloride (NiCl2·6H2O), and 35g of boric acid (H3BO3) in a magnetic stirrer, add one liter of deionized water, and stir for a certain period of time to make it evenly dissolved. Then add 10g of complexing agent solution sodium citrate to help nickel ions deposit evenly. Add 0.3g of brightener nickel sulfate to make the surface brightness of the electroplated layer higher and more uniform. Then add 0.3g of wetting agent potassium isooctyl sulfonate and pH adjuster ammonia water to improve the quality of the plating layer and process stability, and control the acid-base environment. The pH value of the electroplating solution is adjusted to 4.0 and the temperature is controlled at 60°C.
[0106] S202, put the pretreated carbonyl iron powder into a nickel plating electrolytic cell, and keep the plating solution temperature at 60°C. The electroplating adopts a DC power supply, and the current density is controlled at 2A / dm 2 , the electroplating time is 60 minutes. During the electroplating process, the electroplating solution is evenly stirred using a filter. The filter capacity is 15 liters / minute, and a PP filter cartridge is used. The electrolytic cell temperature is 55°C. The electroplating solution needs to be continuously stirred using a filter to ensure uniform deposition of the nickel coating on the surface of the carbonyl iron powder. After the electroplating is completed, the nickel-plated carbonyl iron powder is removed from the electrolytic cell using a filter.
[0107] S203, washing the nickel-plated carbonyl iron powder with deionized water for 3 times, 2 minutes each time, to remove the plating solution residue. Then, drying the washed carbonyl iron powder at 100° C. for 30 minutes until the carbonyl iron powder is completely dry.
[0108] S3, post-processing
[0109] S301. In order to improve the bonding strength and corrosion resistance of the nickel coating and the carbonyl iron powder matrix, the dried nickel-plated carbonyl iron powder is placed in a vacuum drying oven and heat treated at 400° C. for 11 hours. After the heat treatment, the carbonyl iron powder is naturally cooled to room temperature.
[0110] S302, placing the heat-treated carbonyl iron powder in a passivation solution containing potassium molybdate (potassium molybdate concentration is 100 g / L) and soaking at room temperature for 15 minutes. After passivation, the carbonyl iron powder is washed with deionized water and dried again.
[0111] S4. Result detection
[0112] Scanning electron microscope observation showed that a uniform and dense nickel layer was formed on the surface of the nickel-plated carbonyl iron powder. After the nickel-plated carbonyl iron powder was immersed in artificial seawater (3.5% NaCl solution) for 1000 hours, no obvious corrosion was found. Further electromagnetic wave absorption performance tests showed that the nickel-plated carbonyl iron powder had good absorption performance in the radar wave frequency band (2-18GHz), meeting the application requirements of radar wave absorbers.
[0113] Figure 3 (a) to (d) are the results of electromagnetic parameter tests of the sample in Example 2 before and after seawater corrosion. It can be seen that after seawater corrosion, the real and imaginary parts of the dielectric constant and the real and imaginary parts of the magnetic permeability of the sample have almost not changed, indicating that after being coated with a nickel coating, the nickel-coated carbonyl iron powder corroded by seawater still maintains excellent electromagnetic parameter characteristics.
[0114] Example 3
[0115] S1. Pretreatment of carbonyl iron powder
[0116] S101. Select carbonyl iron powder with an average particle size of 20 microns and a purity of 99.5%, which is suitable for the production of radar wave absorbers.
[0117] S102, place 150 grams of carbonyl iron powder in 700 milliliters of hydrochloric acid solution, the concentration of the hydrochloric acid solution is 10%. Soak for 8 minutes at room temperature (about 25°C). The purpose of pickling is to remove oxides and other impurities on the surface of the carbonyl iron powder. After the pickling is completed, the carbonyl iron powder is taken out of the acid solution and washed with deionized water 3 times, each time for 2 minutes, to ensure that the residual acid and impurities on the surface of the carbonyl iron powder are completely removed.
[0118] S103, placing the cleaned carbonyl iron powder in a drying oven, and drying it at 10°C and a vacuum pressure of 0.01 MPa for 30 minutes until the surface of the carbonyl iron powder is completely dry. This is to prevent the carbonyl iron powder from being oxidized or corroded.
[0119] S2. Nickel plating of carbonyl iron powder
[0120] S201. Place 300g of nickel sulfate (NiSO4·6H2O), 60g of nickel chloride (NiCl2·6H2O), and 40g of boric acid (H3BO3) in a magnetic stirrer, add one liter of deionized water, and stir for a certain period of time to make it evenly dissolved. Then add 15g of complexing agent solution sodium citrate to help nickel ions deposit evenly. Add 0.6g of brightener nickel sulfate to make the surface brightness of the electroplated layer higher and more uniform. Then add 0.8g of wetting agent sodium isooctyl sulfonate and pH adjuster ammonia water to improve the quality of the coating and process stability, and control the acid-base environment. The pH value of the electroplating solution is adjusted to 5.0 and the temperature is controlled at 50°C.
[0121] S202, put the pretreated carbonyl iron powder into a nickel plating electrolytic cell, and keep the plating solution temperature at 50°C. The electroplating adopts a DC power supply, and the current density is controlled at 10A / dm 2, the electroplating time is 30 minutes. During the electroplating process, the electroplating solution is evenly stirred using a filter. The filter capacity is 15 liters / minute, and a PP filter cartridge is used. The electrolytic cell temperature is 60°C. The electroplating solution needs to be continuously stirred using a filter to ensure uniform deposition of the nickel coating on the surface of the carbonyl iron powder. After the electroplating is completed, the nickel-plated carbonyl iron powder is removed from the electrolytic cell using a filter.
[0122] S203, washing the nickel-plated carbonyl iron powder with deionized water for 3 times, 2 minutes each time, to remove the plating solution residue. Then, drying the washed carbonyl iron powder at 80° C. for 20 minutes until the carbonyl iron powder is completely dry.
[0123] S3, post-processing
[0124] S301. In order to improve the bonding strength and corrosion resistance of the nickel coating and the carbonyl iron powder matrix, the dried nickel-plated carbonyl iron powder is placed in a vacuum drying oven and heat treated at 450° C. for 10 hours. After the heat treatment, the carbonyl iron powder is naturally cooled to room temperature.
[0125] S302, placing the heat-treated carbonyl iron powder in a passivation solution containing ammonium molybdate (ammonium molybdate concentration is 50 g / L) and soaking at room temperature for 20 minutes. After passivation, the carbonyl iron powder is washed with deionized water and dried again.
[0126] S4. Result detection
[0127] Scanning electron microscope observation showed that a uniform and dense nickel layer was formed on the surface of the nickel-plated carbonyl iron powder. After the nickel-plated carbonyl iron powder was immersed in artificial seawater (3.5% NaCl solution) for 1000 hours, no obvious corrosion was found. Further electromagnetic wave absorption performance tests showed that the nickel-plated carbonyl iron powder had good absorption performance in the radar wave frequency band (2-18GHz), meeting the application requirements of radar wave absorbers.
[0128] Example 4
[0129] Except that the complexing agent in S201 is ethylenediaminetetraacetic acid and the brightener is naphthol; the remaining steps are the same as those in Example 2.
[0130] Example 5
[0131] Except that the wetting agent in S201 is sodium dodecyl sulfate, the remaining steps are the same as those in Example 2.
[0132] Example 6
[0133] Except that the wetting agent in S201 is polyvinyl alcohol, the remaining steps are the same as those in Example 2.
[0134] Example 7
[0135] Except that potassium molybdate in S302 is replaced by potassium dichromate, the remaining steps are the same as those in Example 2.
[0136] Example 8
[0137] Except that sodium molybdate in S303 is replaced by sodium dichromate, the remaining steps are the same as those in Example 1.
[0138] Comparative Example 1
[0139] The process of S2 to S3 is not performed, and the pretreated carbonyl iron powder is directly tested by S4.
[0140] Figure 4 (a) to (d) are the electromagnetic parameter test results of the carbonyl iron powder sample obtained in Example 1 that has not been electroplated with nickel before and after seawater corrosion. It can be seen that after seawater corrosion, the real and imaginary values of the sample's dielectric constant have increased significantly, while the real and imaginary values of the sample's magnetic permeability have decreased significantly, indicating that the electromagnetic parameter characteristics of the carbonyl iron powder that has not been coated with nickel have deteriorated after seawater corrosion.
[0141] Comparative Example 2
[0142] No boric acid is added in S201, and the remaining steps are the same as in Example 2.
[0143] Comparative Example 3
[0144] No sodium citrate is added in S201, and the remaining steps are the same as those in Example 2.
[0145] Comparative Example 4
[0146] No potassium isooctyl sulfonate is added in S201, and the remaining steps are the same as those in Example 2.
[0147] Comparative Example 5
[0148] In S201, the pH is adjusted to 7, and the remaining steps are the same as in Example 2.
[0149] Comparative Example 6
[0150] In S201, the pH is adjusted to 2, and the remaining steps are the same as those in Example 2.
[0151] Comparative Example 7
[0152] The current density in S202 is 20A / dm 2 , the remaining steps are the same as those in Example 2.
[0153] Comparative Example 8
[0154] The current density in S202 is 0.5A / dm 2 , the remaining steps are the same as those in Example 2.
[0155] Comparative Example 9
[0156] The heat treatment temperature in S301 is 500° C., and the remaining steps are the same as those in Example 2.
[0157] Comparative Example 10
[0158] 360 g of nickel sulfate (NiSO4·6H2O) was added to S201, and nickel chloride (NiCl2·6H2O) was not added. The remaining steps were the same as those in Example 2.
[0159] Comparative Example 11
[0160] 360 g of nickel chloride (NiCl2·6H2O) was added to S201, and nickel sulfate (NiSO4·6H2O) was not added. The remaining steps were the same as those in Example 2.
[0161] Table 1 Comparison of electromagnetic parameters of various embodiments and comparative examples before and after corrosion (taking 10 GHz as an example)
[0162]
[0163]
[0164] As shown in the data of Table 1, this embodiment ensures that the material will not significantly reduce its microwave magnetic permeability and wave absorption efficiency while improving corrosion resistance by optimizing the thickness and uniformity of the nickel coating through reasonable process control. This embodiment has a simple process and strong stability. The uniform and dense nickel coating containing electroplated Ni coated carbonyl iron powder effectively enhances the corrosion resistance of carbonyl iron powder in harsh marine environments such as high temperature, high humidity and high salt spray content, and extends the service life of the material in the marine environment; this embodiment forms a nickel (Ni) coating layer on the surface of carbonyl iron powder through an electroplating process, and the nickel layer can quickly generate an extremely thin and stable passivation film at room temperature. This passivation film effectively isolates corrosive media such as seawater from direct contact with the iron matrix, thereby significantly improving the corrosion resistance of the material. In addition, the nickel layer, as a cathodic coating, can provide electrochemical protection when it is intact and defect-free. Even when there are small defects locally, the nickel layer will preferentially undergo oxidation reactions and sacrifice itself to protect the iron matrix from corrosion. This sacrificial anode protection mechanism further extends the service life of the material.
[0165] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0166] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant absorbent of electroplated Ni-coated carbonyl iron powder, characterized in that: Follow these steps: S1. Pre-treating the carbonyl iron powder to remove surface oxides and impurities; S2, preparing an electroplating solution containing nickel ions, and depositing a nickel layer on the surface of the carbonyl iron powder by electroplating; S3, performing heat treatment and passivation treatment on the nickel-plated carbonyl iron powder to obtain nickel-coated carbonyl iron powder.
2. The method for preparing a corrosion-resistant absorbent of electroplated Ni-coated carbonyl iron powder according to claim 1, characterized in that: The specific steps of S1 are as follows: S101, soak the carbonyl iron powder in a pickling solution at 25-35°C for 5-10 minutes; S102, washing the pickled carbonyl iron powder with deionized water to remove the acid solution and surface impurities; S103, placing the cleaned carbonyl iron powder in a vacuum drying device, and drying at 80-100° C. for 30-60 minutes, wherein the vacuum pressure during vacuum drying is ≤0.01 MPa.
3. The method for preparing a corrosion-resistant absorbent of electroplated Ni-coated carbonyl iron powder according to claim 2, characterized in that: The pickling solution is composed of hydrochloric acid or sulfuric acid solution with a mass concentration of 10% to 20%.
4. The method for preparing a Ni-coated carbonyl iron powder corrosion resistant absorbent according to claim 1, characterized in that: The specific steps of S2 are as follows: S201, adding nickel salt, buffer and deionized water into a magnetic stirrer for stirring, wherein the stirring rate of the magnetic stirrer is 750-850 rpm and the duration is 30-40 min; Then add complexing agent, brightener and wetting agent in sequence, and finally add pH adjuster to adjust the acid-base environment to between 3-5, and transfer to the electroplating tank after adjustment; S202, placing the carbonyl iron powder pretreated in S1 in an electroplating tank, using a DC power supply for electroplating; and using a filter to circulate the electroplating solution to evenly disperse the electroplating solution; S203, after the nickel plating is completed, the carbonyl iron powder is taken out from the electroplating tank, and is cleaned with deionized water, and then dried after cleaning; the drying temperature is 80-100° C., and the drying time is 20-40 minutes.
5. The method for preparing a Ni-plated carbonyl iron powder corrosion-resistant absorbent according to claim 4, characterized in that: In S201, the nickel salt is a combination of nickel chloride and nickel sulfate; wherein the concentration of nickel sulfate is 200-300 g / L; and the concentration of nickel chloride is 20-60 g / L; The buffer is boric acid with a concentration of 30-40 g / L.
6. The method for preparing a Ni-plated carbonyl iron powder corrosion-resistant absorbent according to claim 4, characterized in that: In S201, the complexing agent is one of sodium citrate and ethylenediaminetetraacetic acid, and the concentration range of the complexing agent addition is 10-15 g / L; The brightener is one of nickel sulfate and naphthol, and the concentration range of the brightener addition is 0.3-0.6 g / L; The wetting agent is any one of isooctyl alcohol sulfonate, sodium dodecyl sulfonate, and polyvinyl alcohol, and the addition amount of the wetting agent is 0.3 g / L to 0.8 g / L; The isooctyl alcohol sulfonation product includes one of sodium isooctyl alcohol sulfonate, potassium isooctyl alcohol sulfonate and isooctyl alcohol sulfonate ester.
7. The method for preparing a Ni-coated carbonyl iron powder corrosion resistant absorbent according to claim 4, characterized in that: During the S202 electroplating process, the current density is controlled at 2-10A / dm 2 The electroplating time is 30 to 60 minutes; the filter cartridge of the filter is made of PP, and the temperature of the electrolytic cell is 50 to 60°C.
8. The method for preparing a Ni-coated carbonyl iron powder corrosion resistant absorbent according to claim 1, characterized in that: The specific steps of S3 are as follows: S301, placing the nickel-plated carbonyl iron powder in a vacuum drying oven for heat treatment, and cooling the carbonyl iron powder to room temperature after the heat treatment; the heat treatment temperature is 350-450° C., and the heat treatment temperature is 10-12 hours; S302, soaking the heat-treated nickel-plated carbonyl iron powder in a passivation solution containing chromate or molybdate for passivation, and then cleaning and drying.
9. The method for preparing a Ni-plated carbonyl iron powder corrosion-resistant absorbent according to claim 8, characterized in that: The concentration of chromate or molybdate in the passivation solution in S302 is 50-150 g / L; The chromate is one of potassium dichromate and sodium dichromate; The molybdate is one of sodium molybdate, potassium molybdate and ammonium molybdate.
10. An electroplated Ni-coated carbonyl iron powder corrosion-resistant absorbent, prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbonyl iron powder composite wave-absorbing material and preparation method thereof
CN112374547A
Rust-resistant carbonyl iron powder wave-absorbing material and preparation method thereof
CN113388231A